THE EFFECTIVENESS OF QUIZ TOWARD STUDENTS MATHEMATICS LEARNING OUTCOMES ON SEVEN GRADE - Novitasari Hariyanti; Aris Thobirin (Universitas Ahmad Dahlan, 2019)
The process of learning mathematics in schools that are still lacking in training students' abilities in solving mathematical problems. Practice questions given are still not enough to train students' ability to solve math problems. Research on giving quizzes aims to improve student learning outcomes. This research is included in experimental research, which intends to determine the differences in students' motivation and mathematics learning outcomes who use quiz learning methods with scientific learning methods. This research was conducted at Junior High School (SMP) Muhammadiyah 2 Minggir, Sleman Regency, with research subjects being grade VII students of Even Semester SMP Muhammadiyah 2 Minggir Academic Year 2017/2018. The research instrument in the form of tests of mathematics learning outcomes in multiple-choice questions. Data analysis using analysis prerequisite test consisting of normality test and homogeneity test. Test hypotheses using an average test. Based on the average test on the test results of mathematics learning, the average value of the experimental class's mathematics learning outcomes was 76.190467. The average value of the mathematics learning outcomes of the control class was 66.84818. This shows differences in the mathematics learning outcomes of the seventh-grade students of SMP Muhammadiyah 2 Minggir Sleman in the even semester of 2017/2018 school year using quiz learning methods with students' mathematics learning outcomes using conventional learning methods. The difference in the average value of learning outcomes of the experimental class and control class is 9,342287, with the average value of the experimental class is higher than the control class. This shows the quiz learning method is more effective in mathematics learning outcomes for students of class VII SMP Muhammadiyah 2 Minggir Kabupaten Sleman even semester 2017/2018 school year.